1997
DOI: 10.1021/es9604828
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Lead-Contaminated Soils:  Role of Synthetic Chelates in Lead Phytoextraction

Abstract: Lead phytoextraction, using plants to extract Pb from contaminated soils, is an emerging technology. Calculations of soil Pb mass balance suggest that this technology will be economically feasible only if systems can be developed to employ high biomass plants that can accumulate greater than 1% Pb in their shoots. In this study, we investigated the potential of adding chelates to Pb-contaminated soils to increase Pb accumulation in plants. The addition of chelates to a Pb-contaminated soil (total soil Pb 2500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
506
3
15

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 875 publications
(556 citation statements)
references
References 23 publications
32
506
3
15
Order By: Relevance
“…Chemically enhanced phytoextraction has been proposed as an effective approach for removing heavy metals from soils using plants (Huang et al, 1997;Blaylock et al, 1997;Liphadzi et al, 2003). Several chelating agents, such as citric acid, EDTA, CDTA, DTPA, EGTA, EDDHA, EDDS, HEDTA and NTA have been tested for their ability to mobilize and increase the accumulation of heavy metals, particularly Pb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemically enhanced phytoextraction has been proposed as an effective approach for removing heavy metals from soils using plants (Huang et al, 1997;Blaylock et al, 1997;Liphadzi et al, 2003). Several chelating agents, such as citric acid, EDTA, CDTA, DTPA, EGTA, EDDHA, EDDS, HEDTA and NTA have been tested for their ability to mobilize and increase the accumulation of heavy metals, particularly Pb.…”
Section: Discussionmentioning
confidence: 99%
“…Most hyperaccumulators, such as Thlaspi, Urtica, Chenopodium, Polygonum sachalase and Alyssim are characterized by slow growth and low-biomass production, which make these plants impractical for use in phytoextraction in the field (Mulligan et al, 2001;Puschenreiter et al, 2001). For this reason, more recent research projects on phytoextraction have focused on high biomass crop species, such as maize (Zea mays), peas (Pisum sativum), oats (Avena sativa), barley (Hordeum vulgare) and Indian mustard (Brassica juncea), and on relevant plant husbandry and soil management practices to enhance the metal uptake of these high biomass species (Blaylock et al, 1997;Huang et al, 1997;Ebbs and Kochian, 1998;Shen et al, 2002;Chen et al, 2004a). Although several conditions must be met in order for phytoremediation to be effective, the bioavailability of metals to plant roots is considered to be a critical requirement for plant uptake to occur (Kayser et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTA and LMWOA can chelate and mobilize the heavy metals in soil, and these two organic acids have been used in decontamination or phytoremediation enhancement of metal polluted soils (Heil et al, 1996;Blaylock et al, 1997;Huang et al, 1997;Wasay et al, 1998). Kedziorek et al (1998) found in the early days that Pb and Cd were readily solved and translocated by EDTA.…”
Section: Effects Of Lmwoa On Soil Solution Chemistrymentioning
confidence: 99%
“…One of the most promising and potentially cost-effective soil remediation techniques is phytoremediation (Ebbs & Kochian, 1997;Huang et al 1997;Blaylock 2000). The ideal plant species to remediate a heavy metal contaminated soil would be a high biomass crop that can both tolerate and accumulate the contaminants of interest.…”
Section: Introductionmentioning
confidence: 99%